2017
DOI: 10.1016/j.drugalcdep.2016.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Oral cannabidiol does not produce a signal for abuse liability in frequent marijuana smokers

Abstract: Background Cannabidiol (CBD) is a naturally occurring constituent of the marijuana plant. In the past few years, there has been great interest in the therapeutic effects of isolated CBD and it is currently being explored for numerous disease conditions (e.g., pain, epilepsy, cancer, various drug dependencies). However, CBD remains a Schedule I drug on the U.S. Controlled Substances Act (CSA). Despite its status, there are no well-controlled data available regarding its abuse liability. Methods Healthy, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 28 publications
5
91
0
1
Order By: Relevance
“…Furthermore, in discrimination studies in rhesus monkeys, CBD did not substitute for a THC discriminative stimulus, indicating the lack of action by CBD at CB 1 receptors [25]. The minimal effects of CBD in this study are similar to those reported by Babalonis et al [13]. Although that study showed few significant effects of CBD, a lower range of doses were used (200, 400, and 800 mg) compared with the present study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, in discrimination studies in rhesus monkeys, CBD did not substitute for a THC discriminative stimulus, indicating the lack of action by CBD at CB 1 receptors [25]. The minimal effects of CBD in this study are similar to those reported by Babalonis et al [13]. Although that study showed few significant effects of CBD, a lower range of doses were used (200, 400, and 800 mg) compared with the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Assessment of the subjective effects of single doses allows one to make conclusions on the "recreational" abuse potential of a drug but does not assess its reinforcing or dependence (physical or psychological) potential. However, the trial was conducted in accordance with the human abuse potential study guidelines, and data presented are generally consistent with other human abuse potential studies of CBD and preclinical data [13,14,33].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…increased heart rate) and psychological (e.g. sedation and self-reported feelings of intoxication) effects of cannabis containing higher levels of THC (Martin-Santos et al 2012; Babalonis et al 2017).…”
Section: Is Cbd Safe?mentioning
confidence: 99%